PROBLEMS IN ASSUMING PROPER RESPONSIBILITY. - McGladrey, I. B. (The Accounting Review, 1947)
The question of the accountant's responsibility was discussed in an article titled "What is the Accountant's Proper Responsibility?," which was published in the November 1946 issue of "Journal of Accountancy." In that article attention was directed to the fact that up to the present an accountant may dodge the responsibility of stating that his examination lacked some of the standard auditing procedures carefully developed over the past fifty years. He may state that he did this and that in the way of verification and omitted something else, but, how is the layman to know whether what he did constitutes an audit on which reliance may be placed. The expression of an opinion by an accountant in connection with financial statements means that it is a financial picture upon which management and third parties may rely. Punishment may be inflicted if he gives this opinion without an adequate examination. But the accountant who makes a superficial examination and who wishes to dodge responsibility for it may hide in a fog of words.